GABAergic inhibition through synergistic astrocytic neuronal interaction transiently decreases vasopressin neuronal activity during hypoosmotic challenge. Issue 8 (13th February 2013) - Wang, Yu‐Feng; Sun, Min‐Yu; Hou, Qiuling; Hamilton, Kathryn A.
Abstract The neuropeptide vasopressin is crucial to mammalian osmotic regulation. Local hypoosmotic challenge transiently decreases and then increases vasopressin secretion. To investigate mechanisms underlying this transient response, we examined the effects of hypoosmotic challenge on the electrical activity of rat hypothalamic supraoptic nucleus (SON) vasopressin neurons using patch‐clamp recordings. We found that 5 min exposure of hypothalamic slices to hypoosmotic solution transiently increased inhibitory postsynaptic current (IPSC) frequency and reduced the firing rate of vasopressin neurons. Recovery occurred by 10 min of exposure, even though the osmolality remained low. The γ‐aminobutyric acid (GABA)A receptor blocker, gabazine, blocked the IPSCs and the hypoosmotic suppression of firing. The gliotoxin l‐aminoadipic acid blocked the increase in IPSC frequency at 5 min and the recovery of firing at 10 min, indicating astrocytic involvement in hypoosmotic modulation of vasopressin neuronal activity. Moreover, β‐alanine, an osmolyte of astrocytes and GABA transporter (GAT) inhibitor, blocked the increase in IPSC frequency at 5 min of hypoosmotic challenge. Confocal microscopy of immunostained SON sections revealed that astrocytes and magnocellular neurons both showed positive staining of vesicular GATs (VGAT). Hypoosmotic stimulation in vivo reduced the number of VGAT‐expressing neurons, and increased co‐localisation and molecular association of VGAT with glial fibrillary acidic protein that increased significantly by 10 min. By 30 min, neuronal VGAT labelling was partially restored, and astrocytic VGAT was relocated to the ventral portion while it decreased in the somatic zone of the SON. Thus, synergistic astrocytic and neuronal GABAergic inhibition could ensure that vasopressin neuron firing is only transiently suppressed under hypoosmotic conditions.